Binders alternative to Portland cement and waste management for sustainable construction – Part 2. Issue 4 (October 2018) - Coppola, Luigi; Bellezze, Tiziano; Belli, Alberto; Bignozzi, Maria C; Bolzoni, Fabio; Brenna, Andrea; Cabrini, Marina; Candamano, Sebastiano; Cappai, Marta; Caputo, Domenico; Carsana, Maddalena; Casnedi, Ludovica; et al.
The paper represents the "state of the art" on sustainability in construction materials. In Part 1 of the paper, issues related to production, microstructures, chemical nature, engineering properties, and durability of mixtures based on binders alternative to Portland cement were presented. This second part of the paper concerns the use of traditional and innovative Portland-free lime-based mortars in the conservation of cultural heritage, and the recycling and management of wastes to reduce consumption of natural resources in the production of construction materials. The latter is one of the main concerns in terms of sustainability since nowadays more than 75% of wastes are disposed of in landfills.